Nursing students' intention to work in rural areas after graduation: a mixed approach study. - Siwakoti,Selina (2021)
ABSTRACT: Introduction: A key constraint to Universal Health Coverage and major problem of health systems of any country is the inequitable distribution of health care workers between rural and urban areas. As intention drives the future action, this study aims to assess the intention of nursing students to work in rural areas and identify the motivating and discouraging factors associated with their intention. Methodology: A cross-sectional study with mixed method was conducted among final year B.Sc. Nursing and BN/BNS students of nursing colleges of Pokhara Metropolitan from December 2020 to July 2021. With ethical approval from ERB of NHRC, a complete enumeration using a self-administered questionnaire for quantitative method and IDIs were done among 4 participants for qualitative method. SPSS was used for analysis of quantitative data. Content analysis was done manually for qualitative data. Results: Only one-third (33.3%) of the participants had the intention to work in rural areas. The motivating factors were opportunity for career advancement (AOR: 3.8; 95% 95% CI: 1.35-10.77), locating near to family (AOR: 3.58, 95% CI: 1.36-9.45), high salary and incentives, high health care needs in rural areas, high prestige whereas discouraging factors were isolation from family and friends (AOR 4.10, 95% CI 1.3412.52), less availability of recreational facilities (AOR 3.68, 95% CI 1.11-12.21), inadequate salary and incentives, lack of equipment and resources, low utilization of skills and knowledge and low self-perceived competency. Conclusion: One-third of the participants had the intention to work in rural areas after graduation. The participants preferred to work staying with or nearby to their family. The enrolment of the students of rural origin/residence or background in nursing program should be ensured. Various motivating factors should be offered to work in rural areas. Keywords: Nursing students, rural area, intention to work, career intention, job location preferences